The influence of pulse-on time and pulse-off time to hardness of aluminum 7075 processed by electrical discharge machining - Moch. Syamsul Ma'arif; Abu Rizal Firdaus; Redi Bintarto; Iis Siti Aisyah (BKS-TM Indonesia, 2025)
This study search at the the hardness of 7075 Aluminum alloy processed in EDM machining by varying pulse-on time and pulse-off time. This study uses an Electrical Discharge Machining (EDM) of C-TEK ZNC 320 Series and the specimens is tested for hardness by a Rockwell Hardness Tester. The material used is Aluminum 7075. EDM is chosen as because it does not require deformation force to perform machining process and suitable for machining of materials that are elastic, easy to form and have high thermal conductivity such as aluminum 7075. The electrode used is copper (Cu) with a diameter of 25.4 mm and a length of 50 mm. The process parameters used are pulse-on time: 50 μs, 75 μs, 100 μs and pulse-off time: 4 μs, 6 μs, 9 μs. The data are consisted of 9 specimens (cells). The results of the average hardness measurements from experiments 1 and 9 are: 28.03 HBR, and 50.80 HBR. Analysis of variance (Anova) shows the calculated F value is 71.55, the